Twelve-Cent Archie New edition with full color illustrations - Beaty, Bart (Comics Culture, 2017)
For over seventy-five years, Archie and the gang at Riverdale High have been America’s most iconic teenagers, delighting generations of readers with their never-ending exploits. But despite their ubiquity, Archie comics have been relatively ignored by scholars—until now. Twelve-Cent Archie is not only the first scholarly study of the Archie comic, it is an innovative creative work in its own right. Inspired by Archie’s own concise storytelling format, renowned comics scholar Bart Beaty divides the book into a hundred short chapters, each devoted to a different aspect of the Archie comics. Fans of the comics will be thrilled to read in-depth examinations of their favorite characters and motifs, including individual chapters devoted to Jughead’s hat and Archie’s sweater-vest. But the book also has plenty to interest newcomers to Riverdale, as it recounts the behind-the-scenes history of the comics and analyzes how Archie helped shape our images of the American teenager. As he employs a wide range of theoretical and methodological approaches, Beaty reveals that the Archie comics themselves were far more eclectic, creative, and self-aware than most critics recognize. Equally comfortable considering everything from the representation of racial diversity to the semiotics of Veronica’s haircut, Twelve-Cent Archie gives a fresh appreciation for America’s most endearing group of teenagers